Efficacy analysis of anterior debridement and bone graft fusion in the treatment of sacroiliac joint tuberculous arthritis: a retrospective analysis of 17 patients - Qi Tian; Cong Peng; Kai Liu; Haopeng Luan; Xiaokang Liu; Linhao Na; Shicong Cao; Zheng Tian (BMC Musculoskeletal Disorders, 2022)
Abstract Background Sacroiliac joint tuberculous arthritis is a relatively rare site of tuberculosis infection, but it can lead to severe sacroiliac joint destruction and dysfunction. Since there are few studies on the surgical methods of sacroiliac joint tuberculosis (SJT), we adopted three different surgical methods based on different degrees of destruction of sacroiliac joint tuberculous arthritis. While revealing its clinical symptoms to improve the diagnostic accuracy, and to determine the safety and feasibility of this surgical approach in the treatment of sacroiliac joint tuberculous arthritis. Methods We retrospectively analyzed 17 patients with tuberculous arthritis of the sacroiliac joint treated by anterior debridement. All these patients underwent anterior debridement of tuberculosis with or without bone graft fusion. Mean postoperative follow-up was 17.2 months (12–25 months). The erythrocyte sedimentation rate (ESR) was used to judge the general situation after surgery, and the fusion of sacroiliac joints was observed by X-ray films and CT scans. And VAS and ODI were used to score to observe postoperative functional recovery. Results Anterior approach debridement is an effective surgical approach for sacroiliac joint tuberculous arthritis. All patients achieved effective relief of lower back and hip pain. The pain was significantly relieved 3 months after the operation, and the pain basically disappeared 6 months after the operation. The erythrocyte sedimentation rate was also significantly reduced after the operation, and it can basically return to the normal level 3 months after the operation. The VAS score and ODI index of the other 16 patients after surgery were significantly lower than those before surgery, except for 1 patient who died of severe type I respiratory failure and septic shock 3 months after surgery, The surviving patients were basically able to achieve stable fusion of the sacroiliac joint at 12 months postoperatively. None of the patients reported significant pain until the last follow-up visit. Conclusions The anterior approach is a very effective surgical method for the treatment of sacroiliac joint tuberculous arthritis, and it is safe and feasible. A clear operative field of view facilitates complete debridement and reduces recurrence, and its function recovers well with stable arthrodesis.